Evaluation of hospital indicators using multicriteria decision analysis (Research, Society and Development, 2022)
Good strategic planning seeks to guide public organizations so that they find opportunities and anticipate threats, and this path is monitored through performance indicators. This study defined criteria based on the perspectives of the BSC to evaluate the performance indicators of a Federal University Hospital. Thus, the work proposed an ordering of the indicators through PROMETHEE-GDSS, in which PROMETHEE II was used in the phases of individual and global assessment, in order to obtain an ordering of net flows. As the main result, it was found that the methodology used provided greater flexibility in the choice of the most relevant Key Performance Indicators (KPIs) that would lead to the achievement of the institutional vision. In addition, the work allowed to indicate a reduction of 50% of the indicators used in the hospital management dashboard, which will allow the monitoring correlated to the organizational strategy.